Incomplete divisions between sister germline cells require Usp8 function - Mathieu, Juliette; Huynh, Jean-René (Comptes Rendus Biologies)
Cytokinetic abscission is the final step of cell division, resulting in two separate daughter cells. While abscission is typically complete across most cell types, germline cells, which produce sexual gametes, do not finish cytokinesis, maintaining connections between sister cells. These connections are essential for sharing cytoplasm as they differentiate into oocyte and sperm. First, we outline the molecular events of cytokinesis during both complete and delayed abscission, highlighting the role of the ESCRT-III proteins. We then focus on recent discoveries that reveal the molecular mechanisms blocking abscission in Drosophila germline cells. The enzyme Usp8 was identified as vital for ensuring incomplete cytokinesis through the regulation of ESCRT-III ubiquitination and localization. Finally, we explore how the processes of incomplete cytokinesis could hold evolutionary importance, suggesting additional studies into choanoflagellates to comprehend the origins of multicellularity.